2016
DOI: 10.1038/srep38387
|View full text |Cite
|
Sign up to set email alerts
|

Th1 cells downregulate connexin 43 gap junctions in astrocytes via microglial activation

Abstract: We previously reported early and extensive loss of astrocytic connexin 43 (Cx43) in acute demyelinating lesions of multiple sclerosis (MS) patients. Because it is widely accepted that autoimmune T cells initiate MS lesions, we hypothesized that infiltrating T cells affect Cx43 expression in astrocytes, which contributes to MS lesion formation. Primary mixed glial cell cultures were prepared from newborn mouse brains, and microglia were isolated by anti-CD11b antibody-conjugated magnetic beads. Next, we prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Reduction of astrocytic Cx43 mRNA levels occurred after treating astrocyte/microglia cocultures but not astrocyte-rich cultures, with interferon (IFN)γ or IL-17, implying that microglia were responsible for this reduction. The authors depicted an IFNγ-mediated microglial release of IL-1β as the causal mechanism (Watanabe et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of astrocytic Cx43 mRNA levels occurred after treating astrocyte/microglia cocultures but not astrocyte-rich cultures, with interferon (IFN)γ or IL-17, implying that microglia were responsible for this reduction. The authors depicted an IFNγ-mediated microglial release of IL-1β as the causal mechanism (Watanabe et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 exists in both mature and immature astrocytes, while Cx30 is expressed only in mature astrocytes ( 31 33 ), thus gliotic scar astrocytes show an upregulation of Cx43 but no detectable changes of Cx30 ( 23 ). Similarly, cultured astrocytes express detectable levels of Cx43 but not Cx30, although they can express Cx30 after very long term culture ( 33 , 34 ). These features of Cx30 make it difficult to study its dynamics and roles in inflammatory demyelination, and therefore there have been few studies of Cx30 in EAE.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we confirmed that Th1 cell‐conditioned media, which contained a high concentration of IFNγ, reduced Cx43 protein levels in mixed glial cell cultures. These findings suggest that Th1 cell‐derived IFNγ activates microglia to release IL‐1β that downregulates Cx43 gap junctions in astrocytes …”
mentioning
confidence: 88%
“…Because it is widely accepted that autoimmune T cells are involved in the pathogenesis of MS, we hypothesized that infiltrating T cells affect Cx43 expression in astrocytes, and that this process contributes to MS lesion extension. We investigated whether CD4 + T cells influence Cx43 protein levels in astrocytes using a primary glial cell culture system …”
mentioning
confidence: 99%